2015
DOI: 10.9710/kjm.2015.31.2.129
|View full text |Cite
|
Sign up to set email alerts
|

Sanitary assessment of the oyster rack culture waters in Wando, Korea

Abstract: To introduce an oyster rack culture in tidal flat of Wando-gun, Korea, we investigated sanitary conditions from 2012 April to 2013 March in oyster growing waters and adjacent area in Wando. Average seawater temperature and salinity ranged 8.6-28.0℃ and 26.2-33.6 psu, respectively. The coliform group and fecal coliform of seawater ranged < 1.8-13.0 MPN/100 mL each. Only one of 60 samples was exceeded in the European criteria of fecal coliform. Influence of adjunct basin's pollution load on cultural waters was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Closed circle (•) indicate the estimated demand for primary production according to Odum (1971). Temporal limitations in nutrient availability were observed for both nitrate and phosphate concentrations adjacent basin did not significantly affect the water quality in the study area, as the pollution load showed half dilution within a radius of 300 m (Kang et al 2015).…”
Section: Resultsmentioning
confidence: 79%
“…Closed circle (•) indicate the estimated demand for primary production according to Odum (1971). Temporal limitations in nutrient availability were observed for both nitrate and phosphate concentrations adjacent basin did not significantly affect the water quality in the study area, as the pollution load showed half dilution within a radius of 300 m (Kang et al 2015).…”
Section: Resultsmentioning
confidence: 79%